THE ROLE OF KOREAN CUISINE IN NEGOTIATING CULTURAL IDENTITY IN MICHELLE ZAUNER’S CRYING IN H MART - Tri Wijayanto, M. Ganjar; Setiawan, Ikwan; Astutiningsih, Irana (Metahumaniora, 2025)
This research discusses Zauner’s journey of identity as a second-generation Korean American diaspora living in America. She wants to negotiate her Korean identity in a dominant society using Korean cuisine as the ultimate gateway. The data for this research were taken from a memoir titled Crying in H Mart by Michelle Zauner, analyzed using Stuart Hall’s Cultural Identity theory, specifically the concepts of being, becoming, and positioning, to clarify how Zauner’s identity journey unfolded. This research aims to reveal the construction of diaspora cultural identity through cultural negotiation, utilizing Korean cuisine as a primary tool to explore cultural heritage. The results of this research indicate that Zauner’s identity is not static but dynamic instead, representing her complex life journey. Before deciding to negotiate her Korean identity, Zauner experienced many things in America, including discrimination that once made her ashamed of her Korean heritage. As she matured, she realized that Korean cuisine was not merely a means of sustenance but a tool for navigating Korean culture within American society. Thus, it becomes evident how the writing in this memoir constructs a framework that reveals the author’s purpose in writing the memoir or the author’s position. There is a construction of soft power diplomacy in her memoir, emphasizing detailed descriptions of cooking methods, serving, and Korean cuisine.